T2-Weighted MRI Detects Presymptomatic Pathology in the SOD1 Mouse Model of ALS. Issue 5 (May 2014) - Evans, Matthew C; Serres, Sébastien; Khrapitchev, Alexandre A; Stolp, Helen B; Anthony, Daniel C; Talbot, Kevin; Turner, Martin R; Sibson, Nicola R
Neuroinflammation has been identified as a potential therapeutic target in amyotrophic lateral sclerosis (ALS), but relevant biomarkers are needed. The superoxide dismutase (SOD1) G93A transgenic mouse model of ALS offers a unique opportunity to study and potentially manipulate presymptomatic pathology. While T 2 -weighted magnetic resonance imaging (MRI) has been shown to be sensitive to pathologic changes at symptom onset, no earlier biomarkers were previously identified and the underlying histopathologic correlates remain uncertain. To address these issues, we used a multimodal MRI approach targeting structural ( T 2, T 2, apparent diffusion coefficient (ADC), magnetization transfer ratio (MTR)), vascular (gadolinium diethylene triamine pentaacetic acid), and endothelial (vascular cell adhesion molecule-microparticles of iron oxide) changes, together with histopathologic analysis from presymptomatic to symptomatic stages of disease. Presymptomatic changes in brainstem nuclei were evident on T 2 -weighted images from as early as 60 days ( P <0.05). Histologic indices of vacuolation, astro- and microglial activation all correlated with T 2 -weighted changes. Significant reductions in ADC ( P <0.01) and MTR ( P <0.05) were found at 120 days in the same brainstem nuclei. No changes in T 1 relaxation, vascular permeability, or endothelial activation were found at any stage of disease. These findings suggest that T 2 -weighted MRI offers the strongest biomarker potential in this model, and that MRI has unique potential for noninvasive and longitudinal assessment of presymptomatically applied therapeutic and neuroprotective agents.